OPTIMASI KOMUNIKASI PADA MASA KEBIJAKAN WORK FROM HOME (WFH) MENGGUNAKAN APLIKASI ZOOM BAGI SISWA PKBM BHAKTI ASIH CILEDUG - Painem Painem; Hari Soetanto (LPPM Universitas Abdurrab, 2021)
One of the policies of the Indonesian Government in preventing the spread of Covid-19 is the work from home (WFH) policy for most institutions and companies. With the reduction of physical activity, interactions at work and communication with various parties must take advantage of technology including telephone, electronic mail, instant messages, and video calls. As a non-formal education institution, PKBM Bhakti Asih has students, most of whom have worked in various fields of work. One of the problems in PKBM Bhakti Asih related to long-distance communication patterns is the unequal technological literacy for all students. Lack of socialization and training to improve technological literacy causes difficulties for students to communicate interactively with many parties, both in work and in teaching and learning. This is the background for the implementation of this community service activity. The main objective of this activity is to improve technological literacy for PKBM Bhakti Asih students in using the Zoom Cloud Meeting application as a means of mass video communication. Participants in this activity involved students and teachers at PKBM Bhakti Asih. Apart from being useful in facilitating teaching and learning activities, for students, of course, this training will be useful in working in their respective companies.